Molecular Survey on Vector-Borne Pathogens in Alpine Wild Carnivorans - Battisti, Elena; Zanet, Stefania; Khalili, Sara; Trisciuoglio, Anna; Hertel, Beatrice; Ferroglio, Ezio (Frontiers in Veterinary Science, 2020)
In Europe, free-ranging wildlife has been linked to the emergence of several vector-borne diseases such as rodents for Borrelia burgdorferi s.l. In particular, wild carnivores are one of the most important sources of emerging zoonotic pathogens worldwide, although little information is available regarding the epidemiology of vector-borne parasites in these animals. Thus, the aim of this paper was to investigate the prevalence of Babesia spp., Anaplasma spp., Ehrlichia spp., Hepatozoon spp. and Leishmania infantum in alpine wild canids and mustelids carnivores from Italy. For this study, spleen samples of 157 foxes (Vulpes vulpes), 45 badgers (Meles meles) and 33 wolves (Canis lupus) collected between from 2009 and 2017 in Northwest Italy were examined by using conventional PCR. Logistic regression model was used to identify possible risk factors for pathogen infection. DNA of any of the tested pathogens was found in more than 90% of the analyzed animals. In particular, Babesia spp. showed significantly higher prevalence in foxes (89.7%) and badgers (89.6%) than in wolves, while the latter were considerably more infected with Hepatozoon canis (75.8%) than foxes (5.1%). None of the badger tested positive for Hepatozoon spp., although they showed high prevalence of Leishmania infantum (53.3%). Sequencing results revealed the presence, among others, of Babesia vulpes, Babesia sp. isolate badger type A and B, and Anaplasma phagocytophilum. Moreover, previously unreported pathogen/host associations were observed, such as Babesia capreoli in wolves and badgers. The prevalence of vector-borne pathogens observed in the present study is one of the highest reported so far, suggesting the importance of free-ranging carnivoranswild carnivores in the epidemiology and maintenance of the sylvatic cycle of these pathogens. Moreover, we highlighted the presence of several species with a considerable impact for human and pet health, such as A. phagocytophilum L. infantum and B. vulpes. Moreover, several of these pathogens are of particular importance regarding human (A. phagocytophilum, L. infantum) and pet health (L. infantum, B. vulpes).